Transformation of Mexican lime with an intron-hairpin construct expressing untranslatable versions of the genes coding for the three silencing suppressors of Citrus tristeza virus confers complete resistance to the virus - Soler, Nuria; Plomer, Montserrat; Fagoaga, Carmen; Moreno, Pedro; Navarro, Luis; Flores, Ricardo; Pena, Leandro (2017)
Citrus tristeza virus (CTV), the causal agent of the most devastating viral disease of citrus, has evolved three silencing suppressor proteins acting at intra- (p23 and p20) and/or intercellular level (p20 and p25) to overcome host antiviral defence. Previously, we showed that Mexican lime transformed with an intron-hairpin construct including part of the gene p23 and the adjacent 3' untranslated region displays partial resistance to CTV, with a fraction of the propagations from some transgenic lines remaining uninfected. Here, we transformed Mexican lime with an intron-hairpin vector carrying full-length, untranslatable versions of the genes p25, p20 and p23 from CTV strain T36 to silence the expression of these critical genes in CTV-infected cells. Three transgenic lines presented complete resistance to viral infection, with all their propagations remaining symptomless and virus-free after graft inoculation with CTV-T36, either in the nontransgenic rootstock or in the transgenic scion. Accumulation of transgene-derived siRNAs was necessary but not sufficient for CTV resistance. Inoculation with a divergent CTV strain led to partially breaking the resistance, thus showing the role of sequence identity in the underlying mechanism. Our results are a step forward to developing transgenic resistance to CTV and also show that targeting simultaneously by RNA interference (RNAi) the three viral silencing suppressors appears critical for this purpose, although the involvement of concurrent RNAi mechanisms cannot be excluded.